A multi-layer patch and its preparation method and application
Through multi-layer patch structure and electrospinning technology, combined with antibacterial and anti-inflammatory substances, the existing patch degradation time is uncontrollable and anti-infective performance is insufficient, and patches are achieved with good absorption, biocompatible and mechanical strength.
Patent Information
- Application Number
- CN202411995583.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The degradation time of existing medical patches in the body is uncontrollable, which may lead to inflammatory reactions and tissue fibrosis, and insufficient anti-infection performance, which poses a risk of infection.
A multi-layer patch structure is adopted, including a mesh spinning layer and an orientation spinning layer, and is prepared by electrospinning technology. The mesh spinning layer contains antibacterial and anti-inflammatory substances, and the oriented spinning layer improves mechanical properties.
The absorbability, biocompatibility, mechanical strength and anti-infection of the patch are achieved, while the degradation time is controllable, reducing the risk of inflammatory reactions and tissue fibrosis.
Smart Images

Figure CN119770734A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of patches, and in particular to a multi-layer patch and a preparation method and application thereof. Background Art
[0002] Medical patches made of synthetic materials are widely used in the medical field. They are mainly used to repair and reinforce human tissues to restore their functions. Medical patches made of synthetic materials include non-absorbable patches, partially absorbable patches and absorbable patches. Non-absorbable patches and partially absorbable patches have poor biocompatibility. After being implanted into the human body as foreign bodies, they are prone to trigger the body's foreign body reaction, leading to inflammation, edema or fibrosis of the tissues around the patches; displacement may also occur, resulting in the need for additional surgery to re-fix or remove the patches.
[0003] At present, absorbable patches at home and abroad are mostly made of polyglycolic acid, polyglycolic acid-carbonate or polylactic acid, but the degradation time is uncontrollable. In order to ensure that the patch maintains sufficient mechanical strength before the tissue is completely repaired, its degradation cycle in the body is much longer than the tissue repair cycle. If the patch exists in the body for too long, it may stimulate the surrounding tissues, causing inflammatory reactions, and may also induce tissue fibrosis, resulting in increased hardness of the surrounding tissues and affecting normal functions. In addition, absorbable patches are also at risk of infection after being implanted into the human body as foreign bodies. Once an infection occurs, it is relatively complicated to handle, and sometimes the patch needs to be removed, which may lead to surgical failure.
[0004] Therefore, it is necessary and urgent to research and develop an absorbable patch with good biocompatibility, good mechanical strength, anti-infection and controllable degradation time.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a multi-layer patch which is absorbable, has good biocompatibility, good mechanical strength, is anti-infective, and has controllable degradation time.
[0007] A second object of the present invention is to provide a method for preparing the above-mentioned multi-layer patch.
[0008] A third object of the present invention is to provide the use of the above-mentioned multi-layer patch or the multi-layer patch prepared by the above-mentioned preparation method in the preparation of products for promoting tissue healing in vivo.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] In a first aspect, the present invention provides a multilayer patch, comprising a mesh spinning layer and an oriented spinning layer disposed on one side of the mesh spinning layer;
[0011] The fiber diameter of the mesh spinning layer is ≤10 μm, and the porosity of the mesh spinning layer is 50% to 80%;
[0012] The oriented spinning layer comprises at least two layers of oriented spinning sheets, and the orientation directions of the oriented fibers of two adjacent layers of the oriented spinning sheets are crossed.
[0013] Furthermore, the crossing angle between the orientation directions of the oriented fibers of two adjacent layers of the oriented spinning sheets is 90±10°.
[0014] Furthermore, the thickness of the multi-layer patch is 0.5 to 2 mm;
[0015] Preferably, the thickness of the oriented spinning layer is 0.1 to 1 mm;
[0016] Preferably, the mesh spinning layer has a thickness of 0.4 to 1 mm.
[0017] Furthermore, the porosity of the oriented spinning layer is 40% to 60%;
[0018] Preferably, the fiber diameter of the oriented spinning sheet is 1 nm to 20 μm. 。
[0019] Furthermore, the mesh spinning layer also includes antibacterial and anti-inflammatory substances;
[0020] Preferably, the antibacterial and anti-inflammatory substance comprises chitosan, a drug or chitosan-drug;
[0021] Preferably, the mesh spinning layer and the oriented spinning layer are both obtained by electrospinning biodegradable materials;
[0022] Preferably, the biodegradable material comprises degradable polyurethane or polylactic acid;
[0023] Preferably, the weight average molecular weight of the degradable polyurethane is 13 to 25W;
[0024] Preferably, the weight average molecular weight of the polylactic acid is 18-30W.
[0025] In a second aspect, the present invention provides a method for preparing the above-mentioned multilayer patch, comprising the following steps:
[0026] A. taking a biodegradable material solution as a spinning solution and preparing a mesh spinning layer by an electrospinning method;
[0027] B. Prepare an oriented spinning sheet on a mesh spinning layer by using an electrospinning method, adjust the electrospinning direction, and sequentially electrospin on the upper oriented spinning sheet to obtain an oriented spinning sheet whose orientation direction intersects with that of the upper oriented spinning sheet to obtain a patch.
[0028] Further, the concentration of the biodegradable material solution is 5% to 25% w / v;
[0029] Preferably, the biodegradable material comprises degradable polyurethane or polylactic acid;
[0030] Preferably, the weight average molecular weight of the degradable polyurethane in the spinning solution used to prepare the mesh spinning layer is 13 to 20W; the weight average molecular weight of the degradable polyurethane in the spinning solution used to prepare the oriented spinning sheet is 18 to 25W;
[0031] Preferably, the weight average molecular weight of the polylactic acid is 18-30W.
[0032] Furthermore, the solvent of the biodegradable material solution includes a single solvent of N,N-dimethylformamide, a single solvent of N,N-dimethylacetamide, a mixed solvent of N,N-dimethylformamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether, or a mixed solvent of N,N-dimethylacetamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether;
[0033] Preferably, the solvent in the spinning solution is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran;
[0034] Preferably, the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 10:1 to 3:7, preferably 10:1 to 1:1.
[0035] Furthermore, the spinning conditions of the mesh spinning layer include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, a push injection speed of the nozzle of 0.05-0.6ml / min, a rotation speed of the receiving device of 100 to 800rpm / min, a distance between the nozzle and the receiving device of 0 to 50mm; and a translation speed of the nozzle of 100 to 500mm / min.
[0036] Preferably, the spinning conditions of the oriented spinning layer include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, a push injection speed of the nozzle of 0.05-0.6ml / min; a rotation speed of the receiving device of 800 to 2800rpm / min, a distance between the nozzle and the receiving device of 0 to 50mm; a translation speed of the nozzle of 200 to 700mm / min;
[0037] Preferably, after step A, the method further comprises immersing the mesh spinning layer in a solution of an antibacterial and anti-inflammatory substance, taking it out and freeze-drying it;
[0038] Preferably, the antibacterial and anti-inflammatory substance comprises chitosan, a drug or chitosan-drug;
[0039] Preferably, the method for preparing the chitosan-drug mixed solution comprises adding the drug to an acetic acid-citric acid solution containing chitosan;
[0040] Preferably, the mass ratio of chitosan to drug in the chitosan-drug solution is 1:0.1-0.5;
[0041] Preferably, the concentration of the acetic acid citric acid is 2±0.5% (w / v);
[0042] Preferably, the method for preparing the acetic acid citric acid solution containing chitosan comprises adding chitosan to 2±0.5% (w / v) acetic acid citric acid and stirring in a water bath until the chitosan is completely dissolved;
[0043] Preferably, the temperature of the water bath is 50-60°C.
[0044] In a third aspect, the present invention provides use of the multi-layer patch or the multi-layer patch prepared by the above-mentioned preparation method in the preparation of a product for promoting tissue healing in vivo.
[0045] The multilayer patch provided by the present invention has a fiber diameter of the mesh spinning layer of ≤10 μm, and cells are more likely to attach to the fibers, which is beneficial to cell proliferation and growth, and increases the cell attachment ability of the mesh spinning layer, which is beneficial to cell proliferation and wound healing. At the same time, the high porosity of the mesh spinning layer can provide more space for cell proliferation, which is beneficial to rapid cell proliferation, and can carry antibacterial and anti-inflammatory substances to achieve antibacterial, analgesic, hemostatic, and scar inhibition effects, and promote tissue repair; the mechanical properties of the multilayer patch of the present invention are improved by at least two layers of oriented spinning layers, which is not easy to be torn and is beneficial to cell proliferation and growth. The patch is overall soft and fit, which solves the technical problems in the prior art that the patch has poor adsorption and attachment ability to tissues, is prone to displacement or separation, and is not conducive to tissue healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 A schematic structural diagram of a multi-layer patch provided in Example 1 of the present invention;
[0048] Figure 2 This is an electron microscope observation image of the mesh spinning layer provided in Example 1 of the present invention.
[0049] Icon: 1-net spinning layer; 2-oriented spinning layer. DETAILED DESCRIPTION
[0050] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0051] The methods and techniques of the present invention are generally performed according to conventional methods well known in the art and as described in various general and more specific references that are cited and discussed throughout the present specification unless otherwise indicated.
[0052] In one aspect, the present invention provides a multi-layer patch, comprising a mesh spinning layer 1 and an oriented spinning layer disposed on one side of the mesh spinning layer 1;
[0053] The fiber diameter of the mesh spinning layer 1 is ≤10 μm, and the porosity of the mesh spinning layer 1 is 50% to 80%;
[0054] The oriented spinning layer includes at least two oriented spinning sheets 2, and the orientation directions of the oriented fibers of two adjacent oriented spinning sheets 2 are crossed.
[0055] Most of the cells that repair tissues are fibroblasts, and the diameter of fibroblasts is generally between 20 and 70 microns. The fiber diameter of the mesh spinning layer is ≤10μm, which is smaller than the cell diameter. Fibroblasts and other cells are easier to attach to the fibers, which is conducive to the rapid proliferation and growth of cells and promotes wound healing. At the same time, the porosity of the mesh spinning layer 1 is 50% to 80%, which can provide more space for cell proliferation, which is conducive to the rapid proliferation of cells, and the pores can carry antibacterial and anti-inflammatory substances to achieve the effect of antibacterial hemostasis and promote tissue repair; at least two layers of oriented spinning layers are used to improve the mechanical properties of the multilayer patch of the present invention, which is not easy to be torn and is conducive to cell migration and proliferation. The patch is soft and fits as a whole. It solves the technical problems in the prior art that the patch is thin and easy to be damaged, and has poor adsorption and adhesion to tissues, which is easy to shift or separate, and cannot promote tissue healing.
[0056] The porosity of the mesh spinning layer 1 may be, but is not limited to, 50%, 53%, 55%, 58%, 60%, 63%, 65%, 68%, 70%, 73%, 75%, 78% or 80%, and may be any value between 50% and 80%.
[0057] In some specific embodiments, the cross angle between the orientation directions of the oriented fibers of two adjacent layers of the oriented spinning sheets (2) is 90±10°, and the mechanical properties are optimal.
[0058] In some specific embodiments, the multi-layer patch has a thickness of 0.5 to 2 mm.
[0059] The thickness of the multi-layer patch may be, but is not limited to, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm or 2 mm, and may also be any value between 0.5 and 2 mm.
[0060] In some specific embodiments, the thickness of the oriented spinning layer is 0.1 to 1 mm.
[0061] The thickness of the oriented spinning layer may be, but is not limited to, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm, and may also be any value between 0.1 and 1 mm.
[0062] In some specific embodiments, the mesh spinning layer 1 has a thickness of 0.4 to 1 mm.
[0063] The thickness of the mesh spinning layer may be, but is not limited to, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm, and may also be any value between 0.4 and 1 mm.
[0064] In some specific embodiments, the porosity of the oriented spinning layer is 40% to 60%.
[0065] The porosity of the oriented spinning layer may be, but is not limited to, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58% or 60%, or any value between 40% and 60%.
[0066] In some specific embodiments, the fiber diameter of the oriented spun sheet 2 is 1 nm to 20 μm.
[0067] Among them, the fiber diameter of the oriented spinning layer 2 can be but is not limited to 1nm, 10nm, 30nm, 50nm, 80nm, 100nm, 300nm, 500nm, 800nm, 1μm, 3μm, 5μm, 8μm, 10μm, 13μm, 15μm, 18μm or 20μm, and can also be any value between 1nm and 20μm.
[0068] In some specific embodiments, the mesh spinning layer 1 also includes antibacterial and anti-inflammatory substances.
[0069] In some specific embodiments, the antibacterial and anti-inflammatory substance includes chitosan, drugs or chitosan-drugs.
[0070] Among them, chitosan is a natural cationic polysaccharide with certain antibacterial activity. In the process of wound healing, it has certain hemostatic properties and promotes the infiltration and migration of neutrophils and macrophages. In the late stage of wound healing, it can inhibit the formation of scars and promote epithelial tissue regeneration. The antibacterial and anti-inflammatory substance can be chitosan, or it can be an antibacterial or analgesic drug. At the same time, chitosan is a good drug release carrier, which prolongs the release time of the drug. It can also be a mixture of chitosan and drugs, that is, a drug with chitosan as a carrier. Chitosan has antibacterial, hemostatic, and scar inhibition. At the same time, as a drug carrier, the drug is gradually released as the chitosan is gradually degraded, and can continue to have anti-infection and / or analgesic effects. The drug can be an antibiotic, such as gentamicin, metronidazole, ciprofloxacin, penicillin, cephalosporin, amoxicillin, cephalosporin, etc.; it can also be an analgesic, such as a local anesthetic or a non-steroidal anti-inflammatory drug, such as lidocaine, ibuprofen or aspirin.
[0071] In some specific embodiments, the mesh spinning layer 1 and the oriented spinning layer 2 are both obtained by electrospinning biodegradable materials. The biodegradable materials can be completely degraded, and there will be no inflammation or other adverse reactions caused by the long-term presence of the patch in the body, and the secondary damage caused by the removal of the patch is also avoided.
[0072] In some specific embodiments, the biodegradable material includes degradable polyurethane or polylactic acid;
[0073] In some specific embodiments, the weight average molecular weight of the degradable polyurethane is 13 to 25W;
[0074] In some specific embodiments, the weight average molecular weight of the polylactic acid is 18-30W.
[0075] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned multilayer patch, comprising the following steps:
[0076] A. taking a biodegradable material solution as a spinning solution and preparing a mesh spinning layer 1 by an electrospinning method;
[0077] B. Prepare an oriented spinning sheet 2 on the mesh spinning layer 1 by using an electrospinning method, adjust the electrospinning direction, and electrospin on the upper oriented spinning sheet 2 in turn to obtain an oriented spinning sheet 2 whose orientation direction intersects with that of the upper oriented spinning sheet 2, thereby obtaining a patch.
[0078] The use of degradable polyurethane allows the patch to be completely degraded while also having excellent mechanical properties and being difficult to break.
[0079] In some specific embodiments, the concentration of the biodegradable material solution is 5% to 25% w / v; in some specific embodiments, the biodegradable material includes degradable polyurethane or polylactic acid.
[0080] In some specific embodiments, the weight average molecular weight of the degradable polyurethane in the spinning solution used to prepare the mesh spinning layer 1 is 13-20 W; the weight average molecular weight of the degradable polyurethane in the spinning solution used to prepare the oriented spinning sheet 2 is 18-25 W; in some specific embodiments, the weight average molecular weight of polylactic acid is 18-30 W. By using polyurethane materials with different molecular weights and combining the patch structure, the degradation rates of the mesh spinning layer and the oriented spinning layer are controlled to match the cell growth and wound healing speed.
[0081] In some specific embodiments, the solvent of the biodegradable material solution includes a single solvent of N,N-dimethylformamide, a single solvent of N,N-dimethylacetamide, a mixed solvent of N,N-dimethylformamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether, or a mixed solvent of N,N-dimethylacetamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether.
[0082] In some specific embodiments, the solvent in the spinning solution is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran.
[0083] In some specific embodiments, the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 10:1 to 3:7.
[0084] The volume ratio of N,N-dimethylformamide to tetrahydrofuran may be, but is not limited to, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 3:1 or 3:7, or any ratio between 10:1 and 3:7, preferably 10:1 to 1:1.
[0085] In some specific embodiments, the spinning conditions of the mesh spinning layer 1 include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, a push injection speed of the nozzle of 0.05 to 0.6ml / min, a rotation speed of the receiving device of 100 to 800rpm / min, a distance between the nozzle and the receiving device of 0 to 50mm; and a translation speed of the nozzle of 100 to 500mm / min.
[0086] In some specific embodiments, the spinning conditions of the oriented spinning layer include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, a push injection speed of the nozzle of 0.05 to 0.6ml / min; a rotation speed of the receiving device of 800 to 2800rpm / min, a distance between the nozzle and the receiving device of 0 to 50mm; a translation speed of the nozzle of 200 to 700mm / min;
[0087] In some specific embodiments, the step A further comprises immersing the mesh spinning layer 1 in a solution of antibacterial and anti-inflammatory substances, and then taking it out and freeze-drying it.
[0088] In some specific embodiments, the antibacterial and anti-inflammatory substance includes chitosan, drugs or chitosan-drugs.
[0089] The preparation method of the chitosan-drug solution comprises adding the drug into an acetic acid citric acid solution containing chitosan; the mass ratio of the chitosan to the drug is 1:0.1-0.5; and the concentration of the acetic acid citric acid is 2±0.5% (w / v).
[0090] The preparation method of the acetic acid citric acid solution containing chitosan comprises adding chitosan to 2±0.5% (w / v) acetic acid citric acid and stirring in a water bath until the chitosan is completely dissolved. The temperature of the water bath is 50-60°C.
[0091] In some specific embodiments, the method further comprises step C of removing the solvent and drying.
[0092] In some specific embodiments, the removing of the solvent comprises freeze drying to remove the solvent or soaking in water for 1 to 10 days to remove the solvent. In some specific embodiments, the drying temperature is 30 to 100°C.
[0093] According to another aspect of the present invention, there is also provided use of the multi-layer patch or the multi-layer patch prepared by the above-mentioned preparation method in preparing a product for promoting tissue healing in vivo.
[0094] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0095] The patches of the following embodiments and comparative examples all adopt the degradable polyurethane biomaterial provided by the Chinese patent application number 201811568720.2.
[0096] Example 1 (two layers of oriented fiber sheets and one layer of mesh spinning layer, one layer is spun first, and then another layer is spun after rotating 90 degrees in the middle)
[0097] A method for preparing a multilayer patch, the method comprising:
[0098] 1. Prepare a degradable polyurethane (PU) solution 1 as a web spinning solution:
[0099] A 25% polyurethane solution was prepared by using a degradable polyurethane (weight average molecular weight Mw of 13W) as a solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as a solvent.
[0100] The ratio of solvents: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.
[0101] The specific preparation operation is as follows:
[0102] (1) Add 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200 ± 100) r / min, and stir evenly.
[0103] (2) Weigh 75 g of polyurethane material and add it to a three-necked flask. Prepare the volume solution according to the solution concentration.
[0104] (3) Stir at room temperature for more than 4 hours to completely dissolve the PU. Let stand for more than 4 hours to remove bubbles and set aside.
[0105] 2. Prepare a degradable polyurethane (PU) solution 2 as an oriented spinning solution:
[0106] A 25% polyurethane solution was prepared by using a degradable polyurethane (weight average molecular weight Mw: 18W) as a solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as a solvent.
[0107] The ratio of solvent: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.
[0108] The specific preparation operation is as follows:
[0109] (1) Add 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200 ± 100) r / min, and stir evenly.
[0110] (2) Weigh 75 g of polyurethane material and add it to a three-necked flask. Different volumes of solution can be prepared according to the amount of solution used.
[0111] (3) Stir at room temperature for more than 4 hours to completely dissolve the PU. Let stand for more than 4 hours to remove bubbles and set aside.
[0112] 3. Electrospinning mesh spinning layer:
[0113] (1) Wipe the electrospinning machine clean and ensure that the equipment is in a clean state.
[0114] (2) Fix the release paper on the receiving device to ensure that the release paper is not loose.
[0115] (3) Adjust the distance between the nozzle and the receiver to 20±1cm, determine the position and tighten it.
[0116] (4) The receiver receiving speed is set to (500±100) rpm / min; the injection speed of the nozzle is set to 0.3±0.05 ml / min.
[0117] The translation speed of the nozzle was set to 200±50mm / min, and the translation distance was set to 300±50mm.
[0118] Use the prepared biodegradable polyurethane (PU) solution 1 and slowly draw the PU solution with a disposable syringe to avoid bubbles. If bubbles are generated, they must be removed before subsequent operations. Install a 22G needle (inner diameter 0.41mm) and fix the syringe in the buckle of the electrospinning machine push pump.
[0119] The nozzle diameter range can be: 0.15-4.2mm, preferably 18G (inner diameter 0.9mm), 19G (inner diameter 0.84mm), 20G (inner diameter 0.62mm), 21G (inner diameter 0.51mm), 22G (inner diameter 0.41mm), 23G (inner diameter 0.33mm), 24G (inner diameter 0.3mm) needles. In this embodiment, a 22G needle is selected.
[0120] The negative voltage was set to (-3±1) KV, and the positive voltage was set to (9±0.5) KV. The first electrospinning was started, and the spinning effect was observed until continuous and uniform filaments were ejected. The electrospinning time was set to 30 min to 2 h. After the spinning was completed, a mesh spinning layer was obtained.
[0121] 4. Impregnation of chitosan-drug mixed solution
[0122] (1) Weigh an appropriate amount of chitosan, dissolve it with 2±0.5% (w / v) acetic acid and citric acid, and stir it in a water bath at 50-60°C until the chitosan is completely dissolved to form a uniform chitosan solution.
[0123] (2) Dissolve the drug in an appropriate amount of deionized water to ensure complete dissolution. Alternatively, the drug may be made into powder and then added to the chitosan solution in powder form.
[0124] (3) Slowly add the dissolved or dispersed drug to the chitosan solution, stirring while adding to ensure that the drug is evenly distributed in the solution. The amount of drug added accounts for 25±5% of the weight of chitosan.
[0125] (4) Immersing the mesh spinning layer in the chitosan-drug mixed solution, and freeze-drying it after it is fully absorbed.
[0126] 5. Electrospinning oriented spinning layer:
[0127] (1) Fix the dried mesh spinning layer with chitosan-drug on the release paper, and then fix the release paper on the receiving device to ensure that the release paper is not loose.
[0128] (2) Adjust the distance between the nozzle and the receiver to 20±1cm, determine the position and tighten it.
[0129] (3) The prepared biodegradable polyurethane (PU) solution 2 was used for the second electrospinning, and some parameters were adjusted as follows: the receiving speed of the receiver was set to (1800±100) rpm / min; the injection speed of the nozzle was set to 0.2±0.05 ml / min.
[0130] The translation speed of the nozzle was set to 500±50mm / min, and the translation distance was set to 300±50mm.
[0131] The electrospinning time is 30min~1h.
[0132] The other parameters are the same as in step 3.
[0133] (4) After the second electrospinning, rotate the release paper 90 degrees and then fix it. Repeat step (3) to perform the third electrospinning. After the electrospinning is completed, a preliminary product of a multilayer patch is obtained.
[0134] 6. Post-processing
[0135] The initial multilayer patch is freeze-dried, inspected for appearance, and then cut into the required size.
[0136] Example 2 (two layers of oriented fiber sheets and one layer of mesh spinning layer, one layer is spun first, and then another layer is spun after rotating 90 degrees in the middle)
[0137] A method for preparing a multilayer patch, the method comprising:
[0138] 1. Prepare a degradable polyurethane (PU) solution 1 as a web spinning solution:
[0139] A 5% polyurethane solution was prepared by using degradable polyurethane (weight average molecular weight Mw: 20W) as solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as solvent.
[0140] The ratio of solvent: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.
[0141] The specific preparation operation is as follows:
[0142] (1) Add 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200 ± 100) r / min, and stir evenly.
[0143] (2) Weigh 15 g of polyurethane material and add it to a three-necked flask. Prepare the volume solution according to the solution concentration.
[0144] (3) Stir at room temperature for more than 4 hours to completely dissolve the PU. Let stand for more than 4 hours to remove bubbles and set aside.
[0145] 2. Prepare a degradable polyurethane (PU) solution 2 as an oriented spinning solution:
[0146] A 5% polyurethane solution was prepared by using degradable polyurethane (weight average molecular weight Mw: 25W) as solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as solvent.
[0147] The ratio of solvents: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.
[0148] The specific preparation operation is as follows:
[0149] (1) Add 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200 ± 100) r / min, and stir evenly.
[0150] (2) Weigh 15 g of polyurethane material and add it to a three-necked flask. Different volumes of solution can be prepared according to the amount of solution used.
[0151] (3) Stir at room temperature for more than 4 hours to completely dissolve the PU. Let stand for more than 4 hours to remove bubbles and set aside.
[0152] 3. Electrospinning mesh spinning layer:
[0153] (1) Wipe the electrospinning machine clean and ensure that the equipment is in a clean state.
[0154] (2) Fix the release paper on the receiving device to ensure that the release paper is not loose.
[0155] (3) Adjust the distance between the nozzle and the receiver to 20±1cm, determine the position and tighten it.
[0156] (4) The receiver receiving speed is set to (500±100) rpm / min; the injection speed of the nozzle is set to 0.3±0.05 ml / min.
[0157] The translation speed of the nozzle was set to 200±50mm / min, and the translation distance was set to 300±50mm.
[0158] Use the prepared biodegradable polyurethane (PU) solution 1 and slowly draw the PU solution with a disposable syringe to avoid bubbles. If bubbles are generated, they must be removed before subsequent operations. Install a 22G needle (inner diameter 0.41mm) and fix the syringe in the buckle of the electrospinning machine push pump.
[0159] The negative voltage was set to (-3±1) KV, and the positive voltage was set to (9±0.5) KV. The first electrospinning was started, and the spinning effect was observed until continuous and uniform filaments were ejected. The electrospinning time was set to 30 min to 2 h. After the spinning was completed, a mesh spinning layer was obtained.
[0160] 4. Impregnation of chitosan-drug mixed solution
[0161] (1) Weigh an appropriate amount of chitosan, dissolve it with 2±0.5% (w / v) acetic acid and citric acid, and stir it in a water bath at 50-60°C until the chitosan is completely dissolved to form a uniform chitosan solution.
[0162] (2) Dissolve the drug in an appropriate amount of deionized water to ensure complete dissolution. Alternatively, the drug may be made into powder and then added to the chitosan solution in powder form.
[0163] (3) Slowly add the dissolved or dispersed drug to the chitosan solution, stirring while adding to ensure that the drug is evenly distributed in the solution. The amount of drug added accounts for 25±5% of the weight of chitosan.
[0164] (4) Immersing the mesh spinning layer in the chitosan-drug mixed solution, and freeze-drying it after it is fully absorbed.
[0165] 5. Electrospinning oriented spinning layer:
[0166] (1) Fix the dried mesh spinning layer with chitosan-drug on the release paper, and then fix the release paper on the receiving device to ensure that the release paper is not loose.
[0167] (2) Adjust the distance between the nozzle and the receiver to 20±1cm, determine the position and tighten it.
[0168] (3) The prepared biodegradable polyurethane (PU) solution 2 was used for the second electrospinning, and some parameters were adjusted as follows: the receiving speed of the receiver was set to (1800±100) rpm / min; the injection speed of the nozzle was set to 0.2±0.05 ml / min.
[0169] The translation speed of the nozzle was set to 500±50mm / min, and the translation distance was set to 300±50mm.
[0170] The electrospinning time is 30min~1h.
[0171] The other parameters are the same as in step 3.
[0172] (4) After the second electrospinning, rotate the release paper 90 degrees and then fix it. Repeat step (3) to perform the third electrospinning. After the electrospinning is completed, a preliminary product of a multilayer patch is obtained.
[0173] 6. Post-processing
[0174] The initial multilayer patch is freeze-dried, inspected for appearance, and then cut into the required size.
[0175] Example 3 (two layers of oriented fiber sheets and one layer of mesh spinning layer, one layer is spun first, and then another layer is spun after rotating 90 degrees in the middle)
[0176] A method for preparing a multilayer patch, the method comprising:
[0177] 1. Prepare a degradable polyurethane (PU) solution 1 as a web spinning solution:
[0178] A 15% polyurethane solution was prepared by using degradable polyurethane (weight average molecular weight Mw: 16W) as solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as solvent.
[0179] The ratio of solvents: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.
[0180] The specific preparation operation is as follows:
[0181] (1) Add 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200 ± 100) r / min, and stir evenly.
[0182] (2) Weigh 45 g of polyurethane material and add it to a three-necked flask. Prepare the volume solution according to the solution concentration.
[0183] (3) Stir at room temperature for more than 4 hours to completely dissolve the PU. Let stand for more than 4 hours to remove bubbles and set aside.
[0184] 2. Prepare a degradable polyurethane (PU) solution 2 as an oriented spinning solution:
[0185] A 15% polyurethane solution was prepared by using degradable polyurethane (weight average molecular weight Mw: 21W) as solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as solvent.
[0186] The ratio of solvents: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.
[0187] The specific preparation operation is as follows:
[0188] (1) Add 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200 ± 100) r / min, and stir evenly.
[0189] (2) Weigh 45 g of polyurethane material and add it to a three-necked flask. Different volumes of solution can be prepared according to the amount of solution used.
[0190] (3) Stir at room temperature for more than 4 hours to completely dissolve the PU. Let stand for more than 4 hours to remove bubbles and set aside.
[0191] 3. Electrospinning mesh spinning layer:
[0192] (1) Wipe the electrospinning machine clean and ensure that the equipment is in a clean state.
[0193] (2) Fix the release paper on the receiving device to ensure that the release paper is not loose.
[0194] (3) Adjust the distance between the nozzle and the receiver to 20±1cm, determine the position and tighten it.
[0195] (4) The receiver receiving speed is set to (500±100) rpm / min; the injection speed of the nozzle is set to 0.3±0.05 ml / min.
[0196] The translation speed of the nozzle was set to 200±50mm / min, and the translation distance was set to 300±50mm.
[0197] Use the prepared biodegradable polyurethane (PU) solution 1 and slowly draw the PU solution with a disposable syringe to avoid bubbles. If bubbles are generated, they must be removed before subsequent operations. Install a 22G needle (inner diameter 0.41mm) and fix the syringe in the buckle of the electrospinning machine push pump.
[0198] The negative voltage was set to (-3±1) KV, and the positive voltage was set to (9±0.5) KV. The first electrospinning was started, and the spinning effect was observed until continuous and uniform filaments were ejected. The electrospinning time was set to 30 min to 2 h. After the spinning was completed, a mesh spinning layer was obtained.
[0199] 4. Impregnation of chitosan-drug mixed solution
[0200] (1) Weigh an appropriate amount of chitosan, dissolve it with 2±0.5% (w / v) acetic acid and citric acid, and stir it in a water bath at 50-60°C until the chitosan is completely dissolved to form a uniform chitosan solution.
[0201] (2) Dissolve the drug in an appropriate amount of deionized water to ensure complete dissolution. Alternatively, the drug may be made into powder and then added to the chitosan solution in powder form.
[0202] (3) Slowly add the dissolved or dispersed drug to the chitosan solution, stirring while adding to ensure that the drug is evenly distributed in the solution. The amount of drug added accounts for 25±5% of the weight of chitosan.
[0203] (4) Immersing the mesh spinning layer in the chitosan-drug mixed solution, and freeze-drying it after it is fully absorbed.
[0204] 5. Electrospinning oriented spinning layer:
[0205] (1) Fix the dried mesh spinning layer with chitosan-drug on the release paper, and then fix the release paper on the receiving device to ensure that the release paper is not loose.
[0206] (2) Adjust the distance between the nozzle and the receiver to 20±1cm, determine the position and tighten it.
[0207] (3) The prepared biodegradable polyurethane (PU) solution 2 was used for the second electrospinning, and some parameters were adjusted as follows: the receiving speed of the receiver was set to (1800±100) rpm / min; the injection speed of the nozzle was set to 0.2±0.05 ml / min.
[0208] The translation speed of the nozzle was set to 500±50mm / min, and the translation distance was set to 300±50mm.
[0209] The electrospinning time is 30min~1h.
[0210] The other parameters are the same as in step 3.
[0211] (4) After the second electrospinning, rotate the release paper 90 degrees and then fix it. Repeat step (3) to perform the third electrospinning. After the electrospinning is completed, a preliminary product of a multilayer patch is obtained.
[0212] 6. Post-processing
[0213] The initial multilayer patch is freeze-dried, inspected for appearance, and then cut into the required size.
[0214] Example 4
[0215] The difference from Example 1 is that when making two layers of oriented fiber sheets, one layer of oriented fiber sheets is spun first, rotated 60 degrees in the middle, and then another layer of oriented fiber sheets is spun.
[0216] Example 5
[0217] Steps 1-4 are the same as in Example 1.
[0218] In step 5, (1) to (3) are the same as those in Example 1.
[0219] Different from Example 1, after the third electrospinning to produce the oriented fiber sheet is completed, the release paper is rotated 90 degrees and then fixed. Step (3) is repeated to perform the fourth electrospinning.
[0220] After the fourth electrospinning, the release paper is rotated 90 degrees and then fixed. Step (3) is repeated for the fifth electrospinning. After the electrospinning is completed, a preliminary multi-layer patch (four layers of oriented fiber sheets and one mesh spinning layer) is obtained.
[0221] Example 6
[0222] The difference from Example 1 is that polylactic acid is used instead of degradable polyurethane (PU), and the weight average molecular weight of the polylactic acid is 25W.
[0223] Comparative Example 1
[0224] The difference from Example 1 is that the oriented spinning layer is replaced by two mesh spinning layers, and no oriented fiber layer is prepared.
[0225] Comparative Example 2
[0226] The difference from Example 1 is that the mesh spinning layer is replaced by a layer of oriented spinning sheet, and the chitosan-drug mixed solution is impregnated in the layer of oriented spinning sheet.
[0227] Comparative Example 3
[0228] The difference from Example 1 is that the mesh spinning layer is not impregnated with the chitosan-drug mixed solution.
[0229] Test 1 Mechanical properties test
[0230] The mechanical properties of the patches of Examples 1 to 6 and Comparative Examples 1 to 2 were tested respectively according to the following methods, and the specific operations included:
[0231] (1) Tensile strength: The dry samples to be tested were first cut into multiple specimens with appropriate width, flat edges, parallel sides and no visible defects. Then, the tensile testing machine was turned on, the parameters were set, the tensile strength test was performed, and the data was processed. The specific results are shown in Table 1.
[0232] Tensile strength (N / cm) = tension (N) / sample width (cm).
[0233] (2) Elongation at break: First, the dry sample to be tested was cut into multiple specimens with appropriate width, flat edges, parallel sides and no visible defects. Then, the tensile testing machine was turned on, the parameters were set, the elongation at break test was performed, and the data was processed. The specific results are shown in Table 1.
[0234] Elongation at break (%) = (elongation at break of sample / original length of sample) × 100%.
[0235] (3) Suture strength: First, the dry sample to be tested was cut into multiple specimens with appropriate width, flat edges, parallel sides and no visible defects. Then, a suture thread of the selected specification was used to sew one end of the sample to be tested with two needles and tied to fix it. The same method was used to sew multiple specimens, and the thickness of each sample was tested with a thickness gauge. Then, a tensile testing machine was used to clamp the sample to be tested and test the suture strength of the suture to obtain the test data. The specific results are shown in Table 1.
[0236] (4) Tear strength: First, cut the dry sample to be tested into samples with appropriate width, flat edges, parallel sides and no visible defects. Use a cutter to cut along the center of the sample to prepare a trouser-shaped sample. The cutting edge of the cutter must be kept sharp without curling or notching. The cut is located in the center of the sample width. Use a thickness gauge to measure 3 points in the tear area of the sample, and the arithmetic average is the thickness. Turn on the tensile testing machine, clamp the sample to be tested, and perform a tear strength test to obtain the test data. The specific results are shown in Table 1.
[0237] (5) Bursting strength: First, the dry test sample was cut into multiple square specimens with appropriate width, flat edges, parallel sides and no visible defects. The thickness of each sample was tested with a thickness gauge. Then, the tensile testing machine was turned on and the test sample was clamped to perform the bursting strength test. The test data was obtained. The specific results are shown in Table 1.
[0238] Table 1 Mechanical properties test results of different patches
[0239]
[0240] It can be seen from Table 1 that the mechanical properties of Example 1 are better than those of Comparative Example 1 (no oriented fiber layer, only 3 layers of mesh spinning layers). From the comparison of the data of Example 4 and Example 1, it can be seen that the closer the cross angle of the orientation direction of the two layers of oriented spinning sheets in the oriented fiber layer is to 90 degrees, the more balanced the mechanical properties of the patch in the transverse and longitudinal directions are. The tensile strength of the degradable repair patch of the present invention reaches 15.05-34.32N / cm, the elongation at break reaches 100.52-293.53%, the suture strength reaches 5.56-14.26N, the tear strength reaches 10.32-27.53N, and the bursting strength reaches 101.25-297.03kPa. The multi-layer patch of the present invention has good mechanical properties and can well meet the mechanical property requirements of the patch for tissue repair.
[0241] Test 2 Antibacterial performance test
[0242] Test samples: the patches of Examples 1 to 6 and Comparative Examples 1 to 3;
[0243] Test method:
[0244] (1) Test subjects: Escherichia coli, Staphylococcus aureus.
[0245] (2) Test method: Antibacterial test:
[0246] (3) Aseptically unpack the samples. Cut each sample into pieces and place each sample fragment into the culture medium. After culturing at 37°C for 24 hours, count the colonies.
[0247] The antibacterial rate calculation formula is: X = (AB) / A × 100%, where X is the antibacterial rate, A is the average colony count before the sample is shaken, and B is the average colony count after the sample is shaken.
[0248] The specific test results are shown in Table 2 (the above tests were conducted three times and the average value was taken):
[0249] Table 2
[0250]
[0251] The antibacterial performance test results in Table 2 show that, compared with Comparative Example 3, Examples 1-6 and Comparative Example 1-2 contain chitosan-drugs and have better antibacterial effects.
[0252] Test 3: Softness test
[0253] The patches of Examples 1 to 6 and Comparative Examples 1 to 2 were respectively taken, and the samples were cut into specimens of 100 mm×100 mm in size, and tested according to the softness determination method in GB / T 8942-2016. The experimental results are shown in Table 3.
[0254] Table 3
[0255] sample Softness / mN sample Softness / mN Example 1 456.46 Example 5 518.87 Example 2 503.24 Example 6 467.29 Example 3 489.55 Comparative Example 1 588.62 Example 4 448.04 Comparative Example 2 420.06
[0256] It can be seen from Table 3 that the patch prepared in the embodiment of the present invention has a softness of 448.04-518.87 mN and has good softness and adhesion.
[0257] Experiment 4 Cell proliferation ability test
[0258] Take the patches of Examples 1 to 6 and Comparative Examples 1 to 2, and perform a cell proliferation test according to the following operation: use a puncher to make each sample into a circular sample of the same size as the bottom area of a 48-well plate, sterilize it, put it into a 48-well cell culture plate, and soak it in MEM culture medium containing 10% FBS at 37°C and 60rpm for 24 hours, with the outer layer of the sample facing the bottom of the well.
[0259] The whole process was performed in a clean bench to ensure aseptic operation. Mouse fibroblast L-929 cells grown to the logarithmic growth phase were digested with 0.25% trypsin (containing EDTA). After digestion, the cell suspension was centrifuged (1000 rpm, 5 min), the supernatant was discarded, and the cells were resuspended in MEM medium and counted to obtain 2×10 4 The soaked samples were spread in 48-well plates, and 3 samples were processed in parallel in each group.
[0260] 2×10 4 300 μL of a cell suspension of 10 cells / mL was seeded into each well of a 48-well plate and cultured in a cell culture incubator (37° C., 5% CO 2 , >90% humidity).
[0261] After 24h, 3d and 6d, the original culture medium in the 48-well plate was discarded, and 30μL of MTT solution (concentration of 5mg / mL) was added to the corresponding wells of the 48-well plate, and the plate was placed in a 37°C, 5% carbon dioxide incubator for culture. After 4h, the supernatant was removed, and 200μL of isopropanol was added to each well to dissolve the crystals. After the crystals were completely dissolved, the sample was taken out, and the liquid in the well was transferred to a 96-well plate, 100μL per well, and the absorbance value at a wavelength of 570nm was measured on an ELISA instrument, and compared with the OD value of the blank group, to determine whether the cells had a proliferation effect on the surface of the material, and to calculate its cell proliferation rate. The results are shown in Table 4.
[0262] Table 4 Cell proliferation rate
[0263]
[0264] It can be seen from Table 4 that Examples 1 to 6 have very good cell proliferation rate effects, and the cell proliferation rate effect of the two-layer fiber oriented sheet is more significant.
[0265] Test 5 Degradation test
[0266] The patches of Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to degradation tests according to the following procedures:
[0267] (1) Preparation of enzyme buffer:
[0268] Prepare a solution containing potassium dihydrogen phosphate and disodium hydrogen phosphate with sterile double distilled water, containing 1.653g KH2PO4 and 7.744g NaH2PO4 per liter of buffer. The pH value of the buffer solution should be 7.4±0.2. After sterilization, add 0.2g / L lipase. The salts used in the preparation are analytically pure and dried to constant weight.
[0269] (2) Degradation test:
[0270] The sample is vacuum dried at room temperature to constant weight, and the weight of the sample is accurately measured. The sample is placed in a glass container, covered with enzyme buffer and the container is sealed. The minimum volume of the buffer should be 10 mL, and the ratio of the volume of the buffer (mL) to the mass of the sample (g) should be greater than or equal to 30:1. The sample is maintained at 37 ± 1 ° C in a constant temperature water bath or oven.
[0271] (3) Determination of degradation cycle:
[0272] For sample degradation testing, samples were taken at 17 weeks, 18 weeks, 19 weeks, 21 weeks, 22 weeks, 23 weeks, 24 weeks, 25 weeks, 26 weeks, 23 weeks and 34 weeks for mechanical property testing.
[0273] After wiping the liquid on the sample surface with a paper towel, the sample was loaded into the tensile testing machine fixture and tested directly. The test rate was set to 50 mm / min. The test was terminated when the sample could not be tested for mechanical properties, and the time point for stopping the test was the degradation cycle of the sample. The results are shown in Table 5.
[0274] Table 5 Degradation test results
[0275] sample Test cycle / week sample Test cycle / week Example 1 18W Example 6 18W Example 2 25W Comparative Example 1 12W Example 3 22W Comparative Example 2 19W Example 4 18W Comparative Example 3 18W Example 5 34W
[0276] As can be seen from Table 5, the multilayer patch prepared by the present invention can be completely degraded within 18 to 34 weeks, which can provide sufficient strength support for tissue repair to meet clinical needs, and the patch does not exist in the body for too long.
[0277] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A multi-layer patch, characterized in that: It comprises a mesh spinning layer (1) and an oriented spinning layer arranged on one side of the mesh spinning layer (1); The fiber diameter of the mesh spinning layer (1) is ≤10 μm, and the porosity of the mesh spinning layer (1) is 50% to 80%; The oriented spinning layer comprises at least two layers of oriented spinning sheets (2), and the orientation directions of the oriented fibers of two adjacent layers of the oriented spinning sheets (2) are crossed.
2. The multi-layer patch according to claim 1, characterized in that: The crossing angle between the orientation directions of the oriented fibers of two adjacent layers of the oriented spinning sheets (2) is 90±10°.
3. The multi-layer patch according to claim 1, characterized in that: The thickness of the multi-layer patch is 0.5 to 2 mm; Preferably, the thickness of the oriented spinning layer is 0.1 to 1 mm; Preferably, the mesh spinning layer (1) has a thickness of 0.4 to 1 mm.
4. The multi-layer patch according to claim 3, characterized in that: The porosity of the oriented spinning layer is 40% to 60%; Preferably, the fiber diameter of the oriented spinning sheet (2) is 1 nm to 20 μm. 。 5. The multi-layer patch according to claim 4, characterized in that: The mesh spinning layer (1) also includes antibacterial and anti-inflammatory substances; Preferably, the antibacterial and anti-inflammatory substance comprises chitosan, a drug or chitosan-drug; Preferably, the mesh spinning layer (1) and the oriented spinning layer (2) are both obtained by electrostatic spinning of biodegradable materials; Preferably, the biodegradable material comprises degradable polyurethane or polylactic acid; Preferably, the weight average molecular weight of the degradable polyurethane is 13 to 25W; Preferably, the weight average molecular weight of the polylactic acid is 18-30W.
6. The method for preparing the multilayer patch according to any one of claims 1 to 5, characterized in that: The following steps are involved: A. taking a biodegradable material solution as a spinning solution and preparing a mesh spinning layer (1) by an electrospinning method; B. Prepare an oriented spinning sheet (2) on a mesh spinning layer (1) by using an electrospinning method, adjust the electrospinning direction, and sequentially electrospin on the upper oriented spinning sheet (2) to obtain an oriented spinning sheet (2) whose orientation direction intersects with that of the upper oriented spinning sheet (2), thereby obtaining a patch.
7. The preparation method according to claim 6, characterized in that: The concentration of the biodegradable material solution is 5% to 25% w / v; Preferably, the biodegradable material comprises degradable polyurethane or polylactic acid; Preferably, the weight average molecular weight of the degradable polyurethane in the spinning solution used to prepare the mesh spinning layer (1) is 13 to 20W; the weight average molecular weight of the degradable polyurethane in the spinning solution used to prepare the oriented spinning sheet (2) is 18 to 25W; Preferably, the weight average molecular weight of the polylactic acid is 18-30W.
8. The preparation method according to claim 7, characterized in that: The solvent of the biodegradable material solution includes a single solvent of N,N-dimethylformamide, a single solvent of N,N-dimethylacetamide, a mixed solvent of N,N-dimethylformamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether, or a mixed solvent of N,N-dimethylacetamide and any one or more of tetrahydrofuran, dichloroethane or dimethyl ether; Preferably, the solvent in the spinning solution is a mixed solvent of N,N-dimethylformamide and tetrahydrofuran; Preferably, the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 10:1 to 3:7, preferably 10:1 to 1:
1.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The spinning conditions of the mesh spinning layer (1) include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, a push injection speed of the nozzle of 0.05-0.6ml / min, a rotation speed of the receiving device of 100 to 800rpm / min, a distance between the nozzle and the receiving device of 0 to 50mm; and a translation speed of the nozzle of 100 to 500mm / min. Preferably, the spinning conditions of the oriented spinning layer include a negative voltage of -1KV to -4KV, a positive voltage of 8KV to 10KV, a push injection speed of the nozzle of 0.05-0.6ml / min; a rotation speed of the receiving device of 800 to 2800rpm / min, a distance between the nozzle and the receiving device of 0 to 50mm; a translation speed of the nozzle of 200 to 700mm / min; Preferably, after step A, the method further comprises immersing the mesh spinning layer in a solution of an antibacterial and anti-inflammatory substance, taking it out and freeze-drying it; Preferably, the antibacterial and anti-inflammatory substance comprises chitosan, a drug or chitosan-drug; Preferably, the method for preparing the chitosan-drug solution comprises adding the drug to an acetic acid-citric acid solution containing chitosan; Preferably, the mass ratio of chitosan to drug in the chitosan-drug solution is 1:0.1-0.5; Preferably, the concentration of the acetic acid citric acid is 2±0.5% (w / v); Preferably, the method for preparing the acetic acid citric acid solution containing chitosan comprises adding chitosan to 2±0.5% (w / v) acetic acid citric acid and stirring in a water bath until the chitosan is completely dissolved; Preferably, the temperature of the water bath is 50-60°C.
10. Use of the multilayer patch according to any one of claims 1 to 5 or the multilayer patch prepared by the preparation method according to any one of claims 6 to 9 in preparing products that promote tissue healing in vivo.
Citation Information
Patent Citations
Degradable polyurethane biological material as well as preparation method and application thereof
CN109851744A